El privilegiado lenguaje del amor en al-Andalus - Salinas Campos, Maximiliano (Romanica Silesiana)
It to not possible to understand the history of the love life in Spain without the oriental experience of al-Andalus. During those days the Baghdad’s way of living and loving illuminated Spain and Europe. Throughout the eight hundred years of the material and spiritual oriental influence of Islam in the Iberian Peninsula, the Peninsula became a space for learning and sharing for Christians and Moors; both perceived themselves as benevolent to and close to each other. It is impossible to negate the inevitable conflicts that affected the two civilizations. However, it is important to highlight the persistence of the mystic and poetic will to cross the limits in order to meet the other one’s wealth. The mystic, Ibn Arabi of Murcia (1165—1240), expressed this motivation in an extraordinary way. Illuminated by Moses, Jesus, and Mohammed at the same time, he affirmed that Allah’s mercy would save all human beings. The poet was everywhere in the Arabic world, until his death in Damascus. His spirit, filled with the al-Andalus love life, will travel later with the Moor emigrants to America, and particularly to Chile. Key words: Love, history, women, Spain, al-Andalus.